Strategi Dan Peranan Kitchen Untuk Meningkatkan Oprasional Di Hotel Best Western Premier The Hive Cawang, Jakarta Timur - Widyarini, Audi; Puspita, Ratna; Candrasari, Ati; Purwanto, Eko Obi; Putra, Nova Yudha Andriansyah (Jurnal Pariwisata Bisnis Digital dan Manajemen, 2022)
The hotel kitchen which functions as a production room that processes food ingredients from raw materials to food ingredients that are ready to be served and sold to hotel guests. What must always be kept clean so that the processed food is not contaminated with germs caused by the equipment used or raw materials used in the kitchen area is responsible for food production within the food & beverage department. This organization shows the positions and titles of kitchen staff from the top to the bottom. By looking at the meaning of the function and role of the kitchen in a hotel, and the parts of the kitchen in the hotel and the organization of staff in the hotel kitchen, the author is interested in taking the title: "Strategy and Role of the Kitchen to Improve Operations at the Best Western Premier Hotel The Hive Cawang , East Jakarta".